Opportunities and Challenges of Public Administration Transformation in the Digital Era - I Wayan Adi Sedana; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Changes in the delivery of government services are driven by digital transformation in public administration, which involves utilizing technologies such as data analytics, artificial intelligence, and process automation to enhance the quality of public services. This research employs a descriptive approach based on a literature review from various sources, including books, scientific articles, and relevant journals, aiming to present a holistic overview of digital transformation in public administration, its opportunities, and challenges. The opportunities include ease of communication and accessibility through the implementation of e-government, open government, and broader data utilization. On the other hand, challenges include limitations in managing digital technology and issues related to data security. The digital revolution in public administration has significantly impacted government operations and public services. Digital technology enhances accessibility in various sectors such as politics, governance, health, education, and economics. This transformation fosters transparency, effectiveness, public participation, and data-driven decision-making. Moreover, digital transformation creates opportunities to establish a more open and transparent government, while simultaneously raising challenges related to human rights, privacy, and data protection.